Assessment of Antibiotic Resistance in Escherichia coli Isolated from Various Environmental and Community Sources - Mohammed Asim Ismael (Academia One, 2025)
The rising trend of antibiotic resistance among Escherichia coli (E. coli) is a public health concern of considerable magnitude. This study examines the antibiotic resistance profiles of E. coli strains isolated from multiple environmental and community sources. Collections involved water, soil, sewage, and clinical material from rural and urban areas. The susceptibility of the strains to antibiotic was tested using disk diffusion assay with 12 of the most frequently encountered antibiotics. The resistance rates were analyzed and potential correlations with environmental factors—e.g., degrees of pollution and human activity—were explored. The results showed diversified resistance patterns, with maximum resistance being observed in strains from strongly polluted environments and clinical environments. The study indicates the necessity for strict monitoring of the use of antibiotics and enhanced regulation on the use of antibiotics in order to lower the incidence of resistant strains.
Keywords: Antibiotic resistance; Escherichia coli; Environmental sources; Community sources